COMMUNIST PROPAGANDA AT SCHOOL the world of the reading primers from the soviet bloc, 1949-1989. - Wojdon, Joanna ([S.l.] : ROUTLEDGE, 2021)
Communist Propaganda at School is based on an analysis of reading primers from the Soviet bloc and recreates the world as presented to the youngest schoolchildren who started their education between 1949 and 1989 across the nine Eastern European countries. The author argues that those first textbooks, from their first to last pages, were heavily laden with communist propaganda, and that they share similar concepts, techniques and even contents, even if some national specificities can be observed. This volume reconstructs the image of the world presented to schoolchildren in the first books they were required to read in their school life, and argues that the image was charged with communist propaganda. The book is based on the analysis of over sixty reading primers from nine countries of the Soviet bloc: Albania, Bulgaria, Czechoslovakia, the German Democratic Republic, Hungary, Poland, Romania, the Soviet Union and Yugoslavia from the period. Written with simplicity and straightforwardness, this book will be a valuable resource, not only to international academics dealing with the issues of propaganda, censorship, education, childhood and everyday life under communism in Eastern and Central Europe, but can also academics dealing with education under communism or with the content of primary education. It also brings educational experiences of the Soviet bloc to international researchers, in particular to researchers of education under totalitarian and authoritarian regimes.
OCLC-licensed vendor bibliographic record.
Keywords: Textbook bias -- Europe, Eastern -- History; Education and state -- Europe, Eastern -- History; HISTORY / General; HISTORY / Europe / Eastern; HISTORY / Europe / Former Soviet Republics